Epidemiological Features of Leptospirosis: Ciri-ciri Epidemiologi Leptospirosis - O Sh Ashurov; J A Rakhmanova (Academia Open, 2022)
Leptospirosis, according to the zoonosis control program adopted by WHO in 1985, is one of the most significant diseases. This infection, both epidemiologically and epizootologically, is not yet fully controlled and causes significant economic and social damage in many countries of the world. Leptospirosis belongs to the group of zoonotic infectious diseases. It is characterized by an acute onset, symptoms of intoxication, fever, various manifestations of hemorrhagic syndrome, damage to the liver, kidneys and nervous system. The disease was first described by A. Weil in 1886 and N. P. Vasiliev in 1888, after whom it was long called Weil-Vasiliev's disease. The etiology of leptospirosis was established by Japanese researchers R. Inada et al. in 1915. On the territory of our country, the disease was first described in 1927 by V. A. Bashenin under the name "water fever". Highlights: Leptospirosis is a significant zoonotic infectious disease causing economic and social damage worldwide. The disease is characterized by acute onset, fever, hemorrhagic syndrome, and damage to the liver, kidneys, and nervous system. Leptospirosis was first described in 1886 and its etiology was established in 1915, playing a role in the development of a control program. Keywords: Leptospirosis, Zoonotic infectious disease, Weil-Vasiliev's disease, Epidemiology, Control program